Identification of Forest Damage and Critical Land Around the Jeneberang River - Muchtar, Asikin (PT FORMOSA CENDEKIA GLOBAL, 2025)
Forest destruction and critical land are serious problems that have a direct impact on ecosystem stability and potential disasters in watershed areas, including around the Jeneberang River. This study aims to identify the level of forest destruction and distribution of critical land in the area, and analyze its relationship with topographic conditions and land use. The approach used was descriptive quantitative method with Landsat 8 satellite image interpretation techniques and Geographic Information System (GIS) processing. Data were collected through field observations, documentation, and interviews with 15 informants from forestry agencies and surrounding communities. The analysis was conducted using land cover classification, spatial overlay, and damage level scoring based on the Forestry Department's criteria. The results showed that most of the forest damage occurred on steep slopes with a dominance of declining vegetation, while critical land was scattered in the upper and middle watershed areas with a very high level of damage reaching 37% of the total area. The dominant factors causing damage are land use change, illegal logging, and non-official mining activities. In conclusion, this spatial identification of forest degradation and critical land makes an important contribution to watershed rehabilitation planning and data-driven forest protection policy development. The findings also reinforce the urgency of integrated management across sectors to prevent further environmental degradation in strategic catchment areas.